AlertSim - Serbian Contribution to the LSST. Issue Volume 12:Issue S325(2016) (30th May 2017) - Jevremović, Darko; Vujčić, Veljko; Srećković, Vladimir A.; Aleksić, Jovan; Erkapić, Sanja; Milovanović, Nenad
Abstract: We present simulator of alerts for the Large Synoptic Survey Telescope (LSST) developed by Belgrade group. This simulator will be used in testing the functionality of external event brokers/Complex Event Processing (CEP) engines. It is based on current LSST Simulation framework and allows for different classes of objects to be 'alerted'. A Web service based on our simulator is prototyped and can be accessed by developers of brokers/CEP engines.